A DC electric field sensor based on optical waveguide-based field mill - Wei Song; Zhenyu Zhan; Xiaokuo Kou; Manling Dong; Xiaochuan Huang; Weifeng Xin; Zeyan Shi; Shaoqi He; Jiahong Zhang (AIP Advances, 2025)
Based on the Pockels effect of the lithium niobate crystal, an optical field mill DC electric field sensor has been developed. The structural parameters of the rotating shield electrode are optimized by using the COMSOL Multiphysics simulation software. When the inner radius of the shield electrode r = 5 mm, the outer radius R = 25 mm, and the vertical distance between the sensing electrode and the shield electrode d = 2 mm, achieving the maximum modulation field amplitude and optimal performance. Finally, the rotating shield electrode is incorporated with an asymmetric Mach–Zehnder interferometer optical waveguide, resulting in a field mill DC electric field sensor. Experimental results show that the sensor can transfer a DC electric field into an AC electric field with a frequency of 222.2 Hz. The sensitivity of the sensor is determined to be 0.54 mV/(kV/m), with a minimum detectable electric field of 0.37 kV/m. Under a 1 dB compression condition, the maximum undistorted measurable DC electric field Emax is 179.5 kV/m.